2012
DOI: 10.1111/j.1365-3083.2011.02657.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunodiagnostic Value of Combined Detection of Autoantibodies to Tumor‐associated Antigens as Biomarkers in Pancreatic Cancer

Abstract: Previous studies demonstrated that cancer sera contain antibodies, which react with a unique group of autologous cellular antigens called tumour‐associated antigens (TAAs). This study determines whether a panel of TAAs would enhance antibody detection and be a useful approach in pancreatic cancer (PC) detection and diagnosis. The panel of TAAs was composed of six TAAs including p53, p16, p62, survivin, Koc and IMP1 full‐length recombinant proteins. Enzyme‐linked immunosorbent assay (ELISA) was used to detect a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…Furthermore, due to the heterogeneity of tumor and individual immune response, detection of one single autoantibody cannot provide efficient analysis for cancer diagnosis, while combining a panel of autoantibodies can greatly increase diagnosis sensitivity. Our results showed that the combination of 7 autoantibodies achieved good sensitivity as well as reasonable high specificity, which is comparable with other studies obtained through ELISA [41][42][43][44]. Moreover, compared to ELISA, our customized antigen microarray is capable of providing high throughput data by consuming smaller sample amounts.…”
Section: Tablesupporting
confidence: 86%
“…Furthermore, due to the heterogeneity of tumor and individual immune response, detection of one single autoantibody cannot provide efficient analysis for cancer diagnosis, while combining a panel of autoantibodies can greatly increase diagnosis sensitivity. Our results showed that the combination of 7 autoantibodies achieved good sensitivity as well as reasonable high specificity, which is comparable with other studies obtained through ELISA [41][42][43][44]. Moreover, compared to ELISA, our customized antigen microarray is capable of providing high throughput data by consuming smaller sample amounts.…”
Section: Tablesupporting
confidence: 86%
“…So we have assumed that the drawback can be overcome by using a panel of carefully selected TAAs and that different types of cancer may require different panels of TAAs to achieve the sensitivity and specificity required to make immunodiagnosis a feasible adjunct to tumor diagnosis. Our previous publication [ 12 , 31 ] also indicated that TAAs mini-array seems to be supplementary serological markers for the diagnosis of cancer. Many of these antigen-antibody systems are not found to be useful in differentiating cancer and normal control.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported to be a useful approach for cancer detection and diagnosis by detecting autoantibody using recombinant protein [18, 23, 24]. Therefore, we cloned and expressed a CCNY fusion protein in E. coli BL21 (DE3), established an indirect ELISA method, and analyzed the levels of anti-CCNY autoantibodies in the sera of 264 patients with NSCLC who had not yet undergone treatment, 103 patients with tuberculosis, and 89 healthy controls.…”
Section: Discussionmentioning
confidence: 99%